Three-dimensional dispersion entropy for uterine fibroid texture quantification and post-embolization evaluation. (March 2022) - Lebret, Delphine; Gaudêncio, Andreia S.; Hilal, Mirvana; Saib, Sonia; Haidar, Rakelle; Nonent, Michel; Humeau-Heurtier, Anne
Highlights: Uterine fibroids can be treated with uterine fibroid embolization (UFE) procedure. Objectively assessing the benefits of UFE and the quality of life of patients after undergoing UFE is rather challenging. We propose a new multiscale 3 D entropy-based texture analysis method (MDispEn 3 D ). Relationships are found between MDispEn 3 D results for uterine magnetic resonance imaging (MRI) scans and patients' quality of life. MDispE 3 D could help in the prognosis of uterine fibroids and in follow-up evaluation after the embolization. Abstract: Background and Objective: Uterine fibroids are benign tumors that could lead to symptoms complicating a patient's daily life. Those fibroids can be treated using uterine fibroid embolization (UFE), an effective non-surgical procedure. However, objectively quantifying the benefits of such a procedure, and the patient's quality of life, is rather challenging. Methods : With a novel multiscale three-dimensional (3D) entropy-based texture analysis, the multiscale 3D dispersion entropy (MDispEn 3 D ), this work aims to objectively quantify the evolution –  after UFE  –  of patients' health in terms of quality of life, symptoms severity, and sexual function. For this purpose, clinical data and magnetic resonance imaging (MRI) scans of fibroids are analyzed before UFE (D0), ten days after (D10), and six months after (M6). Results : An inverse correlation is observed between MDispEn 3 D entropy values and both size and volume of fibroids. An inverse correlation is also observed between MDispEn 3 D at M6 and the scores of symptoms severity. Moreover, the patient age is found to be related to the relative difference of DispEn 3 D and MDispEn 3 D values, between D0 and M6, translating into an increasing entropy value. Furthermore, we show that history of fibroma plays a role in determining the obtained DispEn 3 D values at D0. Finally, we observe that the lower MDispEn 3 D values at D0, the larger the size of the fibroid at M6. Conclusions : The proposed MDispEn 3 D method - by quantifying fibroid texture - could assist the medical doctors in the prognosis of uterine fibroids and the patients' quality of life assessment post-UFE. It could therefore favor the choice of this treatment compared to other more invasive surgical treatments.